An Issue on Analysis of Digital Public Governance Political Opportunities Structure in Russia: Regional Aspect - A. М. Kaplunenko (Евразийская интеграция: экономика, право, политика, 2019)
The objective of this work is to study ways to analyze public governance digitalization in Russian regions in terms of political opportunities structure. In order to achieve the objective, the following methods were used: political indices analysis (EGDI, EPI, DESI, CPI, NRI, DAI, ‘Digital Russia’ index, digital literacy index), analysis of political power institutional designs in Russian regions, analysis of research works done by leading foreign and Russian sociologists and political scientists and devoted to public governance digitalization and allied subjects, analysis of core papers of such authors as C. Tilly, S. Tarrow and etc. Learning indices is conditioned by the need to define as large as possible number of public governance digitalization parameters, its inter relations and relevance to Russian political system. Appealing to investigations of digitalization researchers and works of C. Tilly, S. Tarrow constitutes a key part of this article, andthe authors’ concepts provide the or etical foundation of the research. Results of this research are expressed in a set of recommendations on including additional indicators for analysis of digital public governance political opportunities structure. These indicators represent whole plurality of political resources essential for gradual realization of public governance digitalization concept on regional level allowing for particular risks caused by public policy in a sub-federal entity. Summary of the study includes author’s notion about probable challenging or modernization of suggested variants of additional indicators in terms of other theoretical concepts and empirical data not included in this paper.